Natalizumab, Fingolimod, and Dimethyl Fumarate Use and Pregnancy-Related Relapse and Disability in Women With Multiple Sclerosis. (15th June 2021) - Yeh, Wei Zhen; Widyastuti, Putu Ayu; Van der Walt, Anneke; Stankovich, Jim; Havrdova, Eva; Horakova, Dana; Vodehnalova, Karolina; Ozakbas, Serkan; Eichau, Sara; Duquette, Pierre; Kalincik, Tomas; Patti, Francesco; et al.
Abstract : Objective: To investigate pregnancy-related disease activity in a contemporary multiple sclerosis (MS) cohort. Methods: Using data from the MSBase Registry, we included pregnancies conceived after December 31, 2010, in women with relapsing-remitting MS or clinically isolated syndrome. Predictors of intrapartum relapse and postpartum relapse and disability progression were determined by clustered logistic regression or Cox regression analyses. Results: We included 1, 998 pregnancies from 1, 619 women with MS. Preconception annualized relapse rate (ARR) was 0.29 (95% confidence interval 0.27–0.32), fell to 0.19 (0.14–0.24) in the third trimester, and increased to 0.59 (0.51–0.67) in early postpartum. Among women who used fingolimod or natalizumab, ARR before pregnancy was 0.37 (0.28–0.49) and 0.29 (0.22–0.37), respectively, and increased during pregnancy. Intrapartum ARR decreased with preconception dimethyl fumarate use. ARR spiked after delivery across all DMT groups. Natalizumab continuation into pregnancy reduced the odds of relapse during pregnancy (odds ratio 0.76 per month [0.60–0.95], p = 0.017). DMT reinitiation with natalizumab protected against postpartum relapse (hazard ratio [HR] 0.11 [0.04–0.32], p < 0.0001). Breastfeeding women were less likely to relapse (HR 0.61 [0.41–0.91], p = 0.016). We found that 5.6% of pregnancies were followed by confirmed disability progression, predicted by higher relapse activity in pregnancy and postpartum. Conclusion: Intrapartum and postpartum relapse probabilities increased among women with MS after natalizumab or fingolimod cessation. In women considered to be at high relapse risk, use of natalizumab before pregnancy and continued up to 34 weeks gestation with early reinitiation after delivery is an effective option to minimize relapse risks. Strategies of disease-modifying therapy use have to be balanced against potential fetal/neonatal complications.